2021
DOI: 10.1136/jitc-2021-002552
|View full text |Cite
|
Sign up to set email alerts
|

Society for Immunotherapy of Cancer (SITC) clinical practice guideline on immunotherapy for the treatment of urothelial cancer

Abstract: A number of immunotherapies have been developed and adopted for the treatment of urothelial cancer (encompassing cancers arising from the bladder, urethra, or renal pelvis). For these immunotherapies to positively impact patient outcomes, optimal selection of agents and treatment scheduling, especially in conjunction with existing treatment paradigms, is paramount. Immunotherapies also warrant specific and unique considerations regarding patient management, emphasizing both the prompt identification and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 141 publications
(102 reference statements)
0
19
0
Order By: Relevance
“…Yet, only fractions of patients are responding or responding long term [ 17 , 18 ]. For urothelial cancer, the initial excitement that checkpoint inhibition may change the management of the disease gave way to disappointment as several phase III trials failed to show improvement over chemotherapy, and clinical trials using seemingly similar immunotherapeutic agents showed inconsistent results [ 19 , 20 , 21 , 22 ]. However, there is still reason for excitement about immunotherapy’s potential, and maximizing patient benefit seems possible.…”
Section: Immune Checkpoint Inhibitors For Cancer Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, only fractions of patients are responding or responding long term [ 17 , 18 ]. For urothelial cancer, the initial excitement that checkpoint inhibition may change the management of the disease gave way to disappointment as several phase III trials failed to show improvement over chemotherapy, and clinical trials using seemingly similar immunotherapeutic agents showed inconsistent results [ 19 , 20 , 21 , 22 ]. However, there is still reason for excitement about immunotherapy’s potential, and maximizing patient benefit seems possible.…”
Section: Immune Checkpoint Inhibitors For Cancer Treatmentmentioning
confidence: 99%
“…PD-L1 detection by IHC is FDA approved and has demonstrated prognostic value in some situations. However, it is mostly unsatisfactory to predict treatment efficacy with patients failing to respond despite PD-L1-positive tumors, and response is observed with patients despite the absence of PD-L1 in the TME [ 19 , 20 , 21 , 30 ].…”
Section: Immune Checkpoint Inhibitors For Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with metastatic urothelial carcinoma (mUC) remain largely incurable despite responses to platinumbased chemotherapy, and more recently immune checkpoint inhibitors (ICIs) [1,2]. Antibody-drug conjugates (ADCs) have lately emerged as another promising therapeutic option in mUC (Table 1).…”
mentioning
confidence: 99%